1998
DOI: 10.1007/s11357-998-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and mitochondrial function in skeletal muscle: Effects of aging and exercise training

Abstract: The rate of oxidative phosphorylation was investigated in isolated mitochondria from hindlimb muscles of young (4.5 mo) and old (26.5 mo) male Fischer 344 rats with or without endurance training. Further, the susceptibility of the muscle mitochondria to exogenous reactive oxygen species was examined. State 3 and 4 respiration, as well as the respiratory control index (RCI), were significantly lower in muscle mitochondria from aged vs. young rats (P<0.05), using either the site 1 substrates malate-pyruvate (M-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 40 publications
5
31
0
1
Order By: Relevance
“…no change, ; significant decrease Oxidative Stress and Exercise in Elderly Subjects muscle tissue after a training period of 16 weeks at 65 % of VO 2max in older adults (mean age 72.6 ± 1.6 years). This decrease may have been due to greater mitochondrial capacity to scavenge free radicals [116][117][118]. Training may also induce modifications in factors that affect mitochondrial free-radical production.…”
Section: Mdamentioning
confidence: 99%
“…no change, ; significant decrease Oxidative Stress and Exercise in Elderly Subjects muscle tissue after a training period of 16 weeks at 65 % of VO 2max in older adults (mean age 72.6 ± 1.6 years). This decrease may have been due to greater mitochondrial capacity to scavenge free radicals [116][117][118]. Training may also induce modifications in factors that affect mitochondrial free-radical production.…”
Section: Mdamentioning
confidence: 99%
“…Lu et al found that although SOD2 activity was increased with aging in skin fibroblasts from humans of under 60 years of age, it actually decreased in later years [63]. In contrast, SOD2 activity was reportedly increased in skeletal muscles of humans [66, 78] and rats [70, 86], or not changed [76, 87] with aging.…”
Section: Introductionmentioning
confidence: 99%
“…Highly reactive chemically, ROS attack cellular structures located near the sites where ROS are generated. Mitochondrial DNA, proteins, and lipids in the inner membrane of mitochondria are thus vulnerable to oxidative damage [12], resulting in generalized organelle dysfunction, defective mitochondrial biosynthesis and poor energy metabolism [13]. …”
Section: Introductionmentioning
confidence: 99%